Schools transitioning towards more climate awareness: A multi-level analysis of climate protection projects in the German school system - Amelie Vogler (Wuppertal Institut für Klima, Umwelt, Energie, 2022)
This thesis conceptualizes the school as a socio-technical system, in which change towards sustainable development and a transition towards more climate awareness are necessary. The multi-level perspective (MLP) framework is applied to the German school system and to climate protection projects (CPPs) as examples of niche activities integrating climate protection (CP) in the school. The thesis utilizes the analytical levels of the MLP (landscape, regime, and niche) and the concept of regulative, cognitive, and normative rules and addresses the question: How do actors in CPPs perceive drivers and barriers for transitioning towards more climate awareness in the German school system? The data were collected through expert interviews and analyzed by conducting a qualitative content analysis. The results show that the German school system is characterized by an inherent rigidity, deep-set normative role dynamics, and an unappreciated role of schools in society. They also highlight the importance of public pressure, strategic CP orientation, and hands-on approaches. CPPs can be a driving force for this in individual schools, but, overall, CP needs to be addressed more systematically in the school and more substantial efforts and reforms are necessary. Highly motivated niche actors play an important role and represent key drivers for such developments. This thesis reveals the complex and systemic nature of the challenges the German school system is faced with. It highlights the difficulties of integrating CP and the importance of substantial and transformative political action. The thesis demonstrates the crucial need to recognize the significance of schools and their actors for society and to integrate new methods and approaches into the school. This thesis also contributes to the body of literature on socio-technical systems and sustainability transitions. It offers an operationalization of the MLP and reveals strengths and limits as well as future research outlooks. – – Die vorliegende Masterarbeit konzipiert die Schule als sozio-technisches System, in dem ein Wandel hin zu nachhaltiger Entwicklung und eine Transition zu mehr Klimabewusstsein notwendig sind. Dabei wird die Mehr-Ebenen-Perspektive (MLP) auf das deutsche Schulsystem und Klimaschutzprojekte (CPPs) als Beispiele für Nischenaktivitäten zur Einbeziehung von Klimaschutz (CP) in der Schule angewandt. Die analytischen Ebenen der MLP und das Konzept der regulativen, kognitiven und normativen Regeln werden eingesetzt und es wird die Frage beantwortet: Wie nehmen die Akteur:innen in CPPs Treiber und Barrieren für eine Transition zu mehr Klimabewusstsein im deutschen Schulsystem wahr? Die Daten wurden durch Expert*innen-Interviews erhoben und mittels einer qualitativen Inhaltsanalyse ausgewertet. Die Ergebnisse zeigen, dass das deutsche Schulsystem besonders starr ist und durch tief verankerte normative Rollendynamiken und eine nicht gewürdigte Rolle der Schule in der Gesellschaft gekennzeichnet ist. Sie weisen auch auf die Bedeutung von öffentlichem Druck, strategischer CP Ausrichtung und praxisnahen Ansätzen hin. CPPs können in einzelnen Schulen eine treibende Kraft sein, aber insgesamt muss CP in der Schule systematischer integriert werden und größere Reformen sind erforderlich. Hochmotivierte Nischenakteur:innen sind entscheidende Antriebskräfte. Die Arbeit zeigt, wie komplex und systemisch die Herausforderungen sind, vor denen das deutsche Schulsystem steht. Sie verdeutlicht die Schwierigkeiten bei der Einbeziehung von CP und die Wichtigkeit von substanziellen und transformativen politischen Maßnahmen. Es wird auch gezeigt, dass die Rolle der Schule für die Gesellschaft anerkannt und neue Methoden und Ansätze in die Schule integriert werden müssen. Zuletzt trägt die Arbeit zur Literatur über sozio-technische Systeme und Nachhaltigkeits-Transitions bei. Sie schlägt eine Operationalisierung der MLP vor und zeigt Stärken und Grenzen sowie zukünftige Forschungsperspektiven auf.
urn:nbn:de:bsz:wup4-opus-80374
Keywords: 330